2011
DOI: 10.1104/pp.111.179838
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Roots and Shoots Show Distinct Temporal Adaptation Patterns toward Nitrogen Starvation  

Abstract: Nitrogen (N) is an essential macronutrient for plants. N levels in soil vary widely, and plants have developed strategies to cope with N deficiency. However, the regulation of these adaptive responses and the coordinating signals that underlie them are still poorly understood. The aim of this study was to characterize N starvation in adult Arabidopsis (Arabidopsis thaliana) plants in a spatiotemporal manner by an integrative, multilevel global approach analyzing growth, metabolites, enzyme activities, and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

36
224
4
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(273 citation statements)
references
References 121 publications
36
224
4
9
Order By: Relevance
“…Wild-type plants compensated for the inhibition of NiR by increasing the activity of GDH that mediates the deamination of Glu. Increased GDH deamination activity has been associated with catabolic processes during starvation (Krapp et al, 2011) and during the response of rice plants to salt stress (Nguyen et al, 2005). The increase in GDH deamination activity seen in wild-type plants during water stress would increase the amounts of 2-oxoglutarate, contributing to the maintenance of the TCA cycle and providing ammonia needed for amino acid synthesis (Miyashita and Good, 2008).…”
Section: Gs Nadh-gogat Gdh Amination [Gdh a ] And Deamination [Gdh mentioning
confidence: 99%
“…Wild-type plants compensated for the inhibition of NiR by increasing the activity of GDH that mediates the deamination of Glu. Increased GDH deamination activity has been associated with catabolic processes during starvation (Krapp et al, 2011) and during the response of rice plants to salt stress (Nguyen et al, 2005). The increase in GDH deamination activity seen in wild-type plants during water stress would increase the amounts of 2-oxoglutarate, contributing to the maintenance of the TCA cycle and providing ammonia needed for amino acid synthesis (Miyashita and Good, 2008).…”
Section: Gs Nadh-gogat Gdh Amination [Gdh a ] And Deamination [Gdh mentioning
confidence: 99%
“…This allows roots to react fast to changes in the nitrate availability. Addition or removal of nitrate from roots causes almost instant changes in root transport systems (Wang et al, 2003;Krapp et al, 2011). So far, only two high affinity nitrate transporter have been characterized in maize; ZmNRT2.1 seems responsible for nitrate uptake by the epidermis and ZmNRT2.2 for loading of nitrate into the xylem (Trevisan et al, 2008).…”
mentioning
confidence: 99%
“…Most of the microarray experiments have been done on plant material deriving from a mixture of different plant parts and tissues; this could complicate the identification of specific responses to N deprivation. The different tasks of specialized plant tissues, such as roots, source leaves, young sink leaves, or senescing leaves, would require very different adaptation strategies to low N (Gifford et al, 2008;Krapp et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrate has profound effects on gene expression, hormone synthesis, and plant growth (Krapp et al, 2011;Krouk et al, 2011;Bouguyon et al, 2012) independent of its assimilation, demonstrating that it is sensed and signals cellular responses. Microarray analyses have shown that nitrate levels rapidly influence the expression of many classes of genes involved in their assimilation and metabolism (Wang et al, 2003;Scheible et al, 2004;Bi et al, 2007;Nero et al, 2009).…”
mentioning
confidence: 99%